Molecular dynamics simulations suggest a mechanism for translocation of the HIV-1 TAT peptide across lipid membranes - Herce, Henry D; Garcia, Angel E (Proceedings of the National Academy of Sciences - PNAS, 2007)
The recombinant HIV-1 Tat protein contains a small region corresponding to residues ⁴⁷YGRKKRRQRR⁵⁷R, which is capable of translocating cargoes of different molecular sizes, such as proteins, DNA, RNA, or drugs, across the cell membrane in an apparently energy-independent manner. The pathway that these peptides follow for entry into the cell has been the subject of strong controversy for the last decade. This peptide is highly basic and hydrophilic. Therefore, a central question that any candidate mechanism has to answer is how this highly hydrophilic peptide is able to cross the hydrophobic barrier imposed by the cell membrane. We propose a mechanism for the spontaneous translocation of the Tat peptides across a lipid membrane. This mechanism involves strong interactions between the Tat peptides and the phosphate groups on both sides of the lipid bilayer, the insertion of charged side chains that nucleate the formation of a transient pore, followed by the translocation of the Tat peptides by diffusing on the pore surface. This mechanism explains how key ingredients, such as the cooperativity among the peptides, the large positive charge, and specifically the arginine amino acids, contribute to the uptake. The proposed mechanism also illustrates the importance of membrane fluctuations. Indeed, mechanisms that involve large fluctuations of the membrane structure, such as transient pores and the insertion of charged amino acid side chains, may be common and perhaps central to the functions of many membrane protein functions.